Comprehensive transcriptomics and proteomics analyses of pollinated and parthenocarpic litchi (Litchi chinensis Sonn.) fruits during early development - Wei Liu (Nature Portfolio, 2017)
Abstract Litchi (Litchi chinensis Sonn.) is an important fruit that is widely cultivated in tropical and subtropical areas. In this study, we used RNA-Seq and iTRAQ technologies to compare the transcriptomes and proteomes of pollinated (polLFs) and parthenocarpic (parLFs) litchi fruits during early development (1 day, 2 days, 4 days and 6 days). We identified 4,864 DEGs in polLFs and 3,672 in parLFs, of which 2,835 were shared and 1,051 were specifically identified in parLFs. Compared to po1LFs, 768 DEGs were identified in parLFs. iTRAQ analysis identified 551 DEPs in polLFs and 1,021 in parLFs, of which 305 were shared and 526 were exclusively identified in parLFs. We found 1,127 DEPs in parLFs compared to polLFs at different stages. Further analysis revealed some DEGs/DEPs associated with abscisic acid, auxin, ethylene, gibberellin, heat shock protein (HSP), histone, ribosomal protein, transcription factor and zinc finger protein (ZFP). WGCNA identified a large set of co-expressed genes/proteins in polLFs and parLFs. In addition, a cross-comparison of transcriptomic and proteomic data identified 357 consistent DEGs/DEPs in polLFs and parLFs. This is the first time that protein/gene changes have been studied in polLFs and parLFs, and the findings improve our understanding of litchi parthenocarpy.